Implementation of Arabic Language Learning in Sociolinguistic Contexts at Darussalam Sumani Islamic Boarding School - Rahmadewi, Sintya; Srirehani, Melinda Dewi; Mustofa, Syaiful (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study examines the implementation of Arabic language learning within a sociolinguistic context at Darussalam Sumani Islamic boarding school. Arabic is not only a means of conveying religious teachings, but also serves to understand linguistic phenomena that appear in society. This research aims to explore the mastery of Arabic through social factors around it. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation. The object of the research was 30 students of the Darussalam Sumani Solok Islamic boarding school. Data analysis was carried out using mailes and hubberman techniques, collecting data, analyzing data, displaying/describing data and conclusions. Findings reveal that social factors such as talent, interest, and motivation significantly influence students' mastery of Arabic. Talent refers to natural potential, while interest and motivation are shaped by environmental and educational support. The study concludes that integrating social factors into teaching strategies can enhance Arabic language learning outcomes.